GENERALIZATIONS OF STEFFENSEN’S INEQUALITY VIA n WEIGHT FUNCTIONS - Aglić Aljinović, Andrea; Pečarić, Josip; Perušić Pribanić, Anamarija (Matematichki Bilten, 2014)
New generalizations of Steffensen’s inequality are obtained by means of weighted Montgomery identity with \(n\) different weight functions. Instead for a nondecreasing (1-convex) function our generalization hold for a \(n\)-convex function. Further, functionals associated to these new generalizations are observed and used to generate \(n\)-exponentially and exponentially convex functions as well as to obtain new Stolarsky type means related to these functionals.